HUBUNGAN PAPARAN PESTISIDA DENGAN GANGGUAN PERKEMBANGAN ANAK USIA 3-5 TAHUN DI DESA GIRIREJO KECAMATAN NGABLAK KABUPATEN MAGELANG - Nisa Zakiyah; Onny Setiani; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Families of farmer are the one who have risk of exposure to pesticides, especially for those who had children. Children have low tolerance to toxic substances than adults. Exposure to pesticides in children can lead to developmental disorders. This study aims to analyze the relationship of pecticides exposure with developmental disorders of children. The study was conducted on 65 mothers who have children aged 3-5 years in Girirejo Village, Ngablak Sub District Magelang District. This research was an observational-analytic with cross sectional approach. The instrument used is the third edition of Ages and Stages Questioner by Squires, J & Bricker, D. Analysis using chi square. The results of the study were 43.1% of children experiencing developmental disorders according to different aspects which are communication, motoric, problem solving, and personal social. The result of chi square analysis showed that the p value of variables was location of residence (p = 0,385), child activity (p = 0,031), pesticide storage (p = 0,017), pesticide mixing (p = 1.00), years of work (p = 0,52), work hours / day (p = 1.17), and use of PPE (p = .003). The results of this study can be concluded that there are significant relationship between child activity, pesticide storage, and the use of PPE with developmental disorders of children aged 3-5 years in Girirejo Village Ngablak Sub District Magelang District.